2001
DOI: 10.1021/jp004002h
|View full text |Cite
|
Sign up to set email alerts
|

Microsolvation of the Phenol Cation (Ph+) in Nonpolar Environments:  Infrared Spectra of Ph+−Ln (L = He, Ne, Ar, N2, CH4)

Abstract: Infrared photodissociation spectra of several phenol-L n cation clusters (Ph + -L n ; L ) He, Ne, Ar, N 2 , CH 4 ) are recorded in the vicinity of the O-H stretch vibration (ν 1 ) of bare Ph + . The Ph + -L n complexes are produced in an electron impact (EI) ion source, which generates predominantly the most stable isomer of each cluster ion. The spectra of all dimers (n ) 1) show strong ν 1 transitions (at 3537, 3534, 3464, 3365, 3365 cm -1 for L ) He, Ne, Ar, N 2 , CH 4 ), which are attributed to proton-boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
176
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 107 publications
(209 citation statements)
references
References 44 publications
33
176
0
Order By: Relevance
“…As TRA + is expected to form weak H-bonds with nonpolar N 2 molecules, their characteristic features become accessible by direct comparison with the strong conventional H-bond observed in TRA + -H 2 O. The current TRA + -(N 2 ) n study extends our previous characterization of A + -(N 2 ) n clusters with more simple aromatic chromophores (A + ), 32 such as benzene, 33,34 phenols and naphthols, [35][36][37][38][39] anilines, [40][41][42] imidazole, 43 cyclopropenyl, 44,45 and indole (In). 46 These studies revealed that the microsolvation process of acidic aromatic ions in molecular nitrogen is dominated by the competition between two principal binding motifs, namely H-bonding to the acidic functional OH and NH groups and p-stacking to the aromatic ring.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…As TRA + is expected to form weak H-bonds with nonpolar N 2 molecules, their characteristic features become accessible by direct comparison with the strong conventional H-bond observed in TRA + -H 2 O. The current TRA + -(N 2 ) n study extends our previous characterization of A + -(N 2 ) n clusters with more simple aromatic chromophores (A + ), 32 such as benzene, 33,34 phenols and naphthols, [35][36][37][38][39] anilines, [40][41][42] imidazole, 43 cyclopropenyl, 44,45 and indole (In). 46 These studies revealed that the microsolvation process of acidic aromatic ions in molecular nitrogen is dominated by the competition between two principal binding motifs, namely H-bonding to the acidic functional OH and NH groups and p-stacking to the aromatic ring.…”
Section: Introductionsupporting
confidence: 58%
“…46 The blue shaded band profile of the intense n NH band of the H-bound isomer, with a large width of B25 cm À1 and a band origin close to the P-branch head, is typical for the excitation of a proton donor stretch vibration and thus confirms the isomer assignment. 32,37,[53][54][55] The computed structures of the relevant TRA + -N 2 isomers are illustrated in Fig. 3, and important parameters are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…16 MATI, 17 ZEKE, 18 photoionization efficiency (PIE), 19 and IR spectroscopy 20 are consistent with a p-bonded phenol + Á Á ÁAr structure also in the cation ground state. In contrast, the IR photodissociation spectrum of phenol + Á Á ÁAr generated in an electron impact (EI) ion source 21 shows that the most stable isomer in the D 0 state has a H-bound geometry, in line with ab initio calculations. 14,22,23 This has been interpreted by the fact that resonant photoionization of the p-bonded neutral phenol-Ar precursor complex can generate only the p-bonded structure in the cation due to the Franck-Condon principle.…”
Section: Introductionmentioning
confidence: 54%
“…The former can be assigned to n H OH , because its frequency matches with n H OH of ionized PhOH + -Ar. [5][6][7][8] The observation of n H OH indicates the occurrence of p -H isomerization, since the Rydberg states are prepared by Franck-Condon restricted photoexcitation from the p-bound S 1 state. The n H OH frequency observed here (B3490 cm À1 ) is somewhat blue-shifted from that observed for cold PhOH + -Ar clusters generated by collisional aggregation of PhOH + and Ar (n H OH = 3468 cm À1 ).…”
Section: Mati-ir Spectramentioning
confidence: 99%
“…This interaction switching was derived from IR spectra of ionized clusters, PhOH + -Rg, generated by aggregation of Rg atoms following ionization of PhOH, which leads predominantly to the formation of the most stable isomer. [5][6][7][8][9][10][11][12][13] The IR spectra show broad red-shifted hydrogen-bonded OH stretching vibrations (n H OH ) of structures in which the Rg atoms bind to the OH group. Recent high level ab initio calculations have also supported this switching in the interaction motif upon ionization.…”
Section: Introductionmentioning
confidence: 99%